Role of interface hybridization on induced superconductivity in 1T'-WTe₂ and 2H-NbSe₂ heterostructures - Das, Anirban (2023)
Heterostructures between two-dimensional quantum spin Hall insulators (QSHI) and superconducting materials can allow for the presence of Majorana Fermions at their conducting edge states. Although a strong interface hybridization helps induce a reasonable superconducting gap on the topological material, the hybridization can modify the material's electronic structure. In this work, we utilize a realistic low-energy model with tunable interlayer hybridization to study the edge state physics in a heterostructure between monolayer quantum spin Hall insulator 1T$^′$-WTe$_2$ and s-wave superconductor 2H-NbSe$_2$. We find that even in the presence of strong inter-layer hybridization that renders the surface to become conducting, the edge state shows a significantly enhanced local density of states and induced superconductivity compared to the surface. We provide an alternate heterostructure geometry that can utilize the strong inter-layer hybridization and realize a spatial interface between a regime with a clean QSHI gap and a topological conducting edge state.